Application of Hybrid Finite Element-Boundary Integral Algorithm for Solving Electromagnetic Scattering from Multiple Objects over Rough Sea Surface. (13th August 2014) - Xu, Run-Wen; Guo, Li-Xin
Abstract : A hybrid algorithm of the finite element method (FEM) is presented to solve two-dimensional (2D) scattering from multiple dielectric objects above the rough sea surface. Compared with traditional FEM based on approximate absorbing boundaries, FEM based on the boundary integral method (BIM) can reduce the calculational region and solution time of the scattering problem. In the hybrid method, the whole computational region is divided into the sea surface and multiple isolate interior regions for the dielectric objects. FEM is only used to simulate the scattering from multiple interior regions enclosing the objects, whereas the large sea is considered exactly by BIM. The coupled interaction among the isolate interior regions and the sea can be taken into account by BIM. The hybrid technique presented here is efficient and versatile for addressing scattering from multiple arbitrary targets above rough sea surfaces. Scattering properties of multiple dielectric objects above the sea surface under different conditions are discussed in detail.